Modelo de gestión de costos para proyectos en empresas de servicio en tecnologías de información. - Rojas-Burgos, Byron; Canales-Umaña, Francisco; Brenes-Hernández, Hugo (Instituto Tecnológico de Costa Rica, 2011)
Currently, most information technology service companies develop solutions to solve problems and meet the needs of customers through project implementation. Project management has gradually evolved in a positive way in different areas. However, the cost management issue still has many flaws that require not only a process visualization of the costs, but a systemic visualization, taking into account interactions with other areas of organizational support. This study offers an alternative solution to the cost management deficiency, through a model that considers the costs of the processes involved and additionally takes into account the unique characteristics specific to the organization. Finally, it provides a support tool, which in its first version can be used to track and follow up costs, ensuring that they align with the terms of the proposed model.
Proyecto de Graduación (Maestría en Gerencia de Proyectos Empresariales) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, Escuela de Ingeniería en Construcción, Escuela de Ingeniería en Computación, 2011.
Keywords: Riesgos; Contabilidad; Diseño; Control; Oferta y demanda; Gerencia